Effects of Grassland Patches on the Composition and Stability of Soil Aggregates in the Qinghai-Tibet Plateau. Issue 1 (June 2021) - Wang, J; Guo, D
Abstract: Grassland patchiness was an important process in the succession of grassland degradation. The changings of soil aggregates were affected by grassland patches, which in turn affect soil organic carbon mineralization. In this study, the soil aggregates were divided into three particle sizes: macroaggregates (2-0.25mm), microaggregates (0.25-0.053mm) and clay-silt aggregates (<0.053mm) through the wet sieve method. The indoor culture method measured the cumulative mineralization of soil organic carbon. The study analyzed the changes of soil aggregates in the grassland patches of the Qinghai-Tibet Plateau, and the influences of soil aggregates on the soil organic carbon mineralization. The results of the study showed that grassland patches caused significant differences in soil aggregates. Compared with native vegetation, single plant patches and bare area formed by degradation would reduce the stabilities of aggregates and increased the amount of organic carbon mineralization. Soil aggregates of grassland patches have a significant effect on the cumulative mineralization of organic carbon. Therefore, study of changes in soil aggregates and the impacts of aggregates on organic carbon mineralization would help to accurately understand the future carbon cycle of terrestrial ecosystems and climate changes.